Liquid Metal Gallium Micromachines Speed Up in Confining Channels. (6th September 2019) - Wang, Daolin; Lin, Zhihua; Zhou, Chang; Gao, Changyong; He, Qiang
Abstract : One of the great challenges in the field of tiny machines is the capability of engineering liquid metal micromachines to autonomously move within confining channels to perform various complex tasks. Herein, liquid metal gallium micromachines that significantly increase their velocity in confining channels with adaptive deformation under exposure to an electric field are presented. The liquid metal gallium micromachines move toward the negative electrode under the propulsion of hydrogen bubbles, which is obviously different from the previous report that liquid metal gallium alloy (i.e., Galinstan) micromachines move to the positive electrode, owing to the surface tension gradient. More importantly, the liquid metal gallium micromachine can adaptively deform and accelerate in confined channels. The velocity of liquid metal gallium micromachines increases with the decrease in the width of channels. It is found that the speed‐up motion of liquid metal gallium micromachines is caused by the enhanced electro‐osmosis effect in confining channels. The findings not only help understand the role of the confinement effect on the motion of liquid metal micromachines but also provide a novel strategy to manipulate the motion velocity of liquid metal micromachines for specific applications. Abstract : Herein, the effect of confinement on the motion behavior of liquid metal gallium micromachines is investigated. Liquid metal gallium micromachines show an adaptive deformation and speed‐up motion in the confining channels under a direct current electric field. The mechanism of the acceleration of gallium micromachines is the confinement induced in the enhancement of the electro‐osmosis effect.